International migration and occupational licensing an empirical exploration - Durano, Marina Fe B. (The Philippine Review of Economics, 2015)
Occupational licensing has been found to inhibit the geographical mobility of professionals. Previous studies in this area have used data on interstate mobility of professionals in the United States. This work reconsiders occupational licensing in the context of international migration rules. This relationship is relevant under the discussions on the Movement of Natural Persons in the General Agreement on Trade in Services. A conditional logit model and a nested logit model are used to study the relationship between the two types of regulation. The results verify the greater importance of immigration rules over occupational licensing in determining the probability of choosing a destination country for potential foreign providers of engineering services.